Prevalence and associated factors of self-treatment behaviour among different elder subgroups in rural China: a cross-sectional study - Wanchun Xu; Zhong Li; Zijing Pan; Ruibo He; Liang Zhang (BMC, 2020)
Abstract Background Self-treatment is a common and widespread behaviour, of which the risks are multiplied in old age. However, the determinants of self-treatment among elders in rural China remain unclear. This study aims to explore the prevalence and associated factors of self-treatment among elders in rural China, trying to discover the vulnerable groups as well as the service gaps among the rural elders. Methods Based on a multi-stage stratified random sampling method, a cross-sectional household survey was conducted among 30 villages in Sinan County, an impoverished county in western China. Data were collected through a household-individual combined questionnaires. The analysis was restricted to elders who reported illness within the last 2 weeks, and the final sample size was 330 (individuals). Bivariate and multiple logistic regression analysis were performed in the whole sample group and four subgroups to obtain the prevalence ratios regarding the associated factors. Results In the present study, 35.2% of the elders with illness within the last 2 weeks reported self-treatment. The variables associated with self-treatment in the whole sample group were health status (OR 6.75, 95%CI 1.93-23.60), recent alcohol consumption (OR 0.42, 95%CI 0.21-0.83) and the utilisation of family practice services (OR 0.59, 95%CI 0.36-0.96); the same predictors were found in the subgroup of elders with chronic diseases. No significant predictors were found in the subgroup of elders without chronic diseases. Empty-nest elders with higher affinity to traditional Chinese medicine (OR 0.39, 95%CI 0.18-0.86) or drinking alcohol recently (OR 0.28, 95%CI 0.09-0.82) were less likely to self-treat, while the non-empty-nest elders who were no less than 75 years old (OR 3.10, 95%CI 1.33, 7.22) or at better health status (OR 9.20, 95%CI 1.73-48.75) were more likely to self-treat. Conclusion Self-treatment was prevalent among the elders in rural China. Better health status, no recent alcohol consumption and no utilisation of family practice are associated with self-treatment among rural elders. Older elders in the non-empty nest group were more likely to self-treat, while the empty-nest elders with self-care habits in traditional Chinese medicine were less likely to self-treat. Deeper understanding of the self-treatment behaviour among rural elders may provide insights for identifying the potential service gaps and developing improvement strategies in the health care delivery system for the elderly in China.